Niclosamide piperazine solubility in supercritical CO2 green solvent: A comprehensive experimental and modeling investigation - Gholamhossein Sodeifian; Hamidreza Bagheri; Farnoush Masihpour; Negar Rajaei; Maryam Arbab Nooshabadi (Journal of CO2 Utilization)
In order to micro and Nano sizing a drug via supercritical fluid technology, it is necessary to obtain its solubility in various ranges of pressures and temperatures. For this purpose, solubility of Niclosamide piperazine, in supercritical carbon dioxide (SC-CO2) was measured by a new static method, for the first time. The measurements were performed at various circumstances, i.e. temperatures = 308, 318, 328 and 338 K and pressures = 12–27 MPa. The obtained results indicate that pressure significantly influences the solubility of Niclosamide piperazine, with a measured solubility ranging from 0.77 × 10−7 to 13.60 × 10−7 in mole fraction. To study theoretically the solubility of Niclosamide piperazine, the obtained results are modeled using nine semi-empirical equations i.e. Garlapati-Madras, Chrastil, Kumar-Johnston, Sodeifian et al. (models I-II), Bartle et al., Bian et al., Sung-Shim, Mendez-Santiago-Teja and Peng-Robinson EoS with van der Waals mixing rule. Among which the Bian et al., model and Peng-Robinson EoS showed the minimum AARD% of about 4.45 % (corresponding corrected Akaike Information Criterion is −704.09) and 7.54 % (corresponding corrected Akaike Information Criterion is −699.24), respectively. Finally, enthalpies for the binary mixture of Niclosamide piperazine-supercritical carbon dioxide binary system has been determined, for the first time.